Poverty alleviation and peace building in multiethnic societies the need for multiculturist governance in the Philippines - Muslim, Macapado A. (2005)
No different from most of the countries in the world, the Philippines is culturally diverse with its people differing in ethnicity, religion, and language. Similarly, it also shares the problems of effectively managing the challenges of cultural diversity. The Philippine government's approach of assimilation of ethnocultural minorities to mainstream society has proven unsuccessful, as evidenced by the long and ongoing Moro secessionist struggle. And without peace, there is no development--the force provinces in the Autonomous Region in Muslim Mindanao (ARMM) where armed struggle continues are the country's poorest provinces. This study identifies the efforts of the government in managing cultural diversity; however it also stresses that current efforts are not enough and significant stops should be taken by the Philippines towards a multiculturalist governance, a cultural-diversity-friendly political formula whose ends are peace and development.
Keywords: Autonomous Region in Muslim Mindanao; Culture; Governance; Reconciliation; Poverty